2017
DOI: 10.1101/133538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precision Medicine Screening Using Whole Genome Sequencing and Advanced Imaging To Identify Disease Risk in Adults

Abstract: BACKGROUND

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Therefore, the results of our systematic review <0.001 a Data in parentheses are number of studies. b One study 15 did not specify the whole-body MRI and was therefore not included in this subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the results of our systematic review <0.001 a Data in parentheses are number of studies. b One study 15 did not specify the whole-body MRI and was therefore not included in this subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing titles and abstracts of the MEDLINE and Embase databases resulted in 19 studies that were potentially eligible for inclusion. 5,8,11,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] After reviewing the full text, five studies were excluded because data were also used in another article from the same group, comprising a larger number of patients 8,18,25,27,28 ; one study was excluded because it only reported study rationale and design, 22 and one study was excluded because it was not clear whether the head and neck region was included in the FOV. 22 Eventually, 12 studies were included in this systematic review, published between 2005 and 2018.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Untargeted clinical metabolomic profiling of individual patient samples has found early application in the screening of inherited metabolic diseases, 26,37,64,65 but other uses, such as probing of undiagnosed cases for disease insights, as well as health and wellness screenings, have started to emerge. [66][67][68][69][70]…”
Section: Introductionmentioning
confidence: 99%
“…Molecular technologies, including metabolomics (metabolites), transcriptomics (RNA), proteomics (proteins), and epigenomics also have been employed to reveal the functional significance of genomic variations 15,16,17,18 . In particular, the integration of DNA sequencing with metabolomics has proven useful for discoveries of disease-associated genes and biomarkers 19,20,21 .…”
Section: Introductionmentioning
confidence: 99%